1997
DOI: 10.2169/internalmedicine.36.894
|View full text |Cite
|
Sign up to set email alerts
|

Acute Necrotizing Eosinophilic Myocarditis with Giant Cell Infiltration after Remission of Idiopathic Thrombocytopenic Purpura.

Abstract: Acute necrotizing eosinophilic myocarditis is characterized by acute onset, fulminant congestive heart failure, and extensive necrosis of myocytes with striking eosinophilic infiltration. However, multinucleated giant cells sometimes appear in the fulminant phase of severe myocarditis. This is the first case of a patient with a 1 year previous history of idiopathic thrombocytopenic purpura, whopresented with acute necrotizing eosinophilic myocarditis with giant cell infiltration. (Internal Medicine 36: 894-897… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…56,57 Clinically, infiltrating eosinophils are found in severe giant cell myocarditis and these patients, along with necrotizing eosinophilic myocarditis, have poor clinical prognosis. 58,59 Other clinical entities in which moderate levels of eosinophils are found infiltrating the myocardium include hypersensitivity and drug reactions, parasitic infections, vasculitis and granulomatous diseases, and idiopathic hypereosinophilic syndrome. 60 Little is known about the cardiac eosinophil profile; however, in all cases, cardiac necrosis, thrombosis, and fibrosis are found.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Clinically, infiltrating eosinophils are found in severe giant cell myocarditis and these patients, along with necrotizing eosinophilic myocarditis, have poor clinical prognosis. 58,59 Other clinical entities in which moderate levels of eosinophils are found infiltrating the myocardium include hypersensitivity and drug reactions, parasitic infections, vasculitis and granulomatous diseases, and idiopathic hypereosinophilic syndrome. 60 Little is known about the cardiac eosinophil profile; however, in all cases, cardiac necrosis, thrombosis, and fibrosis are found.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, giant cells can appear in eosinophilic myocarditis if the inflammation is severe. Hyogo et al, for example, reported a case of acute necrotizing eosinophilic myocarditis with giant cell infiltration [7]. We diagnosed this case as eosinophilic myocarditis, in spite of the presence of giant cells, for several reasons including the infiltration of the myocardium with numerous eosinophils, the patient's history of allergic disease, and the condition of the patient, which was not as critical as that associated with giant cell myocarditis.…”
Section: Discussionmentioning
confidence: 93%
“…13 The mechanism of damage to the endocardium and later to the myocardium is mediated by the eosinophils' specific granule proteins, such as cationic major basic protein and peroxidase, which accumulate on the endocardial surface. 4 Electrocardiographic abnormalities comprise intraventricular conduction disturbances 15 and ST-T changes 12 with evidence of right or left ventricular hypertrophy. 3,8 Cellular damage to the myocyte is mediated by reactive oxygen species such as hydrogen peroxide released by peroxidase.…”
Section: Discussionmentioning
confidence: 99%